PENGARUH SERTIFIKASI GURU TERHADAP PRESTASI BELAJAR SISWA KLS VIII & IX MTs AL-BATTANI SEPANG - KOTA SERANG - E. Nita Prianti,; Riska Andriani , (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to determine how much influence teacher certification has on student achievement in grades VIII & IX MTs Al-Battani Sepang-Kota Serang. This study uses quantitative methods using statistical data through, simple linear regression test and hypothesis testing or t test. The population in this study was 87. While the sample taken in this study were 47 respondents. The results obtained are that there is a significant effect of teacher certification on student achievement of MTs Al-Battani Serang City. This is evidenced by the results of the calculation of the correlation coefficient that the significance value between teacher certification and student achievement where the significance value ≤ 0.05 is obtained at 0.000 ≤ 0.05. then based on the F test with the acquisition of the value of Fcount = 0.948 while Ftable 2.08 The data obtained means that Fcount ≤ Ftable, namely 0.948 ≤ 2.08. This means that the acquisition data shows the linearity between variable X and variable Y. Furthermore, teacher certification on student learning achievement contributed 41.4% while the remaining 58.4% was influenced by other factors as a contributor to Student Learning Achievement. While the acquisition of t count was 5,791 ≥ t table 2,014. meaning that the results of these data indicate that there is a significant influence between teacher certification and student achievement. This means that Ho is rejected and Ha is accepted.